2016
DOI: 10.15835/buasvmcn-vm:12297
|View full text |Cite
|
Sign up to set email alerts
|

Nigella sativa – a Plant with Personality in Biochemistry and Experimental Medicine Researches

Abstract: Last decades often presented references to traditional medicine, or culinary use of natural resources for a better health status, prevention or treatment of different diseases. One of the natural plants came lately in the researches as a miracle salve: Nigella sativa. Also commonly known as black cumin, the most use of this plant are the seeds, such as, as powder, as oil extract, or as hydro or alcoholic extracts. Culinary usage of N. sativa is referring to the seeds used as spice. Medical usage of this planti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…According to report by Saleh et al 41 , methanol is much more effective in extracting the main bioactive component (TQ) of Nigella sativa at high concentration; and the solvent used for extraction conprised 70% methanol against 30% water. Since it has been earlier reported that the ability of Nigella sativa in scavenging free radicals could be as a result of synergism between its phytochemical components; the much lower protection at high dose could then be as a result of TQ, bearing in mind that its concentration is much more than other phytochemical constituents and this agrees with the reports of AbuKhader, cited in Ahamdi et al 42 , who reported that at 500mg/kg, oral administration of methanol extracts of Nigella sativa became toxic to the rats used for study.…”
Section: Discussionsupporting
confidence: 89%
“…According to report by Saleh et al 41 , methanol is much more effective in extracting the main bioactive component (TQ) of Nigella sativa at high concentration; and the solvent used for extraction conprised 70% methanol against 30% water. Since it has been earlier reported that the ability of Nigella sativa in scavenging free radicals could be as a result of synergism between its phytochemical components; the much lower protection at high dose could then be as a result of TQ, bearing in mind that its concentration is much more than other phytochemical constituents and this agrees with the reports of AbuKhader, cited in Ahamdi et al 42 , who reported that at 500mg/kg, oral administration of methanol extracts of Nigella sativa became toxic to the rats used for study.…”
Section: Discussionsupporting
confidence: 89%
“…Roasted cumin also contains considerable amounts of the substituted 2-methoxy-3-secbutylpyrazine, pyrazines, 2-ethoxy-3isopropylpyrazine and 2-methoxy-3methylpyrazine. Safranal, p-cymene, βpinene, and γ-terpinene are additional ingredients (14). Nigella sativa seeds have a protein content of 26.7%, a fat content of 28.5%, a carbohydrate content of 24.9%, a crude fiber content of 8.4%, and a total ash content (4.8%).…”
Section: Chemical Constituents Of Nigella Sativamentioning
confidence: 99%